Debugger's Handbook, The - DiMarzio, Jerome (CRC Press, 2009)
For today's programmers, it is impossible to foresee every input, every usage scenario, and every combination of applications that can cause errors when run simultaneously. Given all of these unknowns, writing absolutely bug-free code is unachievable. But it is possible, with the right knowledge, to produce nearly bug-free code and The Debugger's Handbook provides just the right guidance to do it.